REPRESENTASI INKLUSIVITAS DALAM TRAILER FILM BARBIE (2023) - Parulian, Nathaniel Antonio; Astagini, Nuria (UI Scholars Hub, 2024)
The humans that God created have different gifts, both physical and intellectual. These differences can create a negative side for members of groups with dark skin color and curly hair, while members with light skin color and straight hair are given a superior position because they are considered capable of creating attractiveness. This condition has become a social phenomenon in society, including in media content. However, something different is shown in one of the content summaries of the Barbie film which will be released in 2023. Several scenes in the Barbie film trailer are a representation of inclusivity which shows that the social phenomenon regarding differences in physical form which has been creating disparities in society is shifting in a positive direction. Through semiotic analysis from Charles Sanders Pierce which became an analytical tool to dissect the visual signs of each scene in the Barbie film trailer, it was found that the setting, characterization, scenario, property, and shooting techniques reflected the inclusive representation in the film trailer. The results of this research show that five scenes represent inclusiveness. The theoretical contribution of this research can be a reference for further research, especially in mass and intercultural communication. In contrast, the applicable contribution can be a guide for the social environment in accepting forms of difference with an open mind.